RESULTS OF INGUINAL HERNIA REPAIRS PERFORMED UNDER LOCAL ANESTHSEIA - Çebi, Kibar; Ocak, İsmail Hakkı (Fırat University, 2001)
Aim: The aim of this study was to investigate the results of inguinal hernia repairs performed under local anesthesia with respect to operation duration, hospitalization period, postoperative complications, need for analgesics, and duration for recovery to normal life style. Material and Methods: Patients admitted to our hospital between January 1998 to January 2001 with diagnose of inguinal hernia were involved in this study. Of these patients whose with cardiovasculary and respiratory problems and those patients without any obvious risk for general anesthesia but voluntered for undergoing inguinal hernia repair under local anesthesia were involved in this study. Results: It was determined that the average operation period was 35-65 minute, hospitalization period 1-3 days, average period of return to work was 10-15 days, and recapture of daily activity 1-3 days, analgesia period, 1-5 days when the inguinal hernia repair operations were performed under local anaesthesia. No systemic or local complications were observed. Conclusion: Lack of systemic or local complications presents advantage of local anesthesia use for inguinal hernia repair. All parameters were in parallel with the literature but average hospitalization period was higher in our study.

Amaç: Bu çalışmada, lokal anestezi ile tamir edilen kasık fıtığı olgularında operasyon süresi, hastanede kalma süresi, postoperatiferatif komplikasyonlar, anal- jezik gereksinimi, ameliyat sonrası işe başlama süresi ve günlük aktiviteyi kazanım süresi yönünden irdelenmesi amaçlanmıştır. Gereç ve Yöntem: Hastanemizde Ocak 1998- Ocak 2001 tarihleri arasında kasık fıtığı tanısı ile tedavi olan olgular içerisinde kardiyovasküler ve respiratuar sorardan olan hastalar ile bilinen hiçbir genel anestezi sorunu olmayıp gönüllü olarak lokal anesteziyi kabul eden hastalar çalışma kapsamına alındı. Bulgular: Lokal anaestezi ile inguinal herni tamirinde ameliyat süresi 35-65 dakika, yatış süresi 1-3 gün, işe başlama süresi 10-15 gün, günlük aktiviteyi kazanım süresi 1-3 gün, ağrı süresi 1-5 gün olarak saptandı. Hastaların hiç birinde lokal ve sistemik komplikasyon gelişmedi. Sonuç: Lokal komplikasyonların olmayışı yanında sistemik komplikasyonların da olmayışı lokal anestezinin bir üstünlüğü olarak değerlendirilebilir. Tüm parametreler literatürle uyumlu olmakla birlikte hastanede kalma süresi bizim serimizde daha uzun olarak tespit edilmiştir.
LOKAL ANESTEZİ İLE YAPILAN İNGUİNAL HERNİ TAMİR SONUÇLARI